Transgovernance : Advancing Sustainability Governance. - Meuleman, Louis (Berlin, Heidelberg : Springer Berlin / Heidelberg, 2012)
This book offers a new context for the sustainability governance debate, transforming classical questions into new options for societal decision making and identifying starting points and strategies for effective governance of transitions to sustainability.
Intro -- Transgovernance -- Advancing Sustainability Governance -- Foreword -- Acknowledgements -- Contents -- Introduction: Transgovernance -- Part 1: Reflections on Sustainability Governance -- Part 2: Sustainability Governance: Topical Themes -- About the Authors -- Author Index -- Subject Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books